1995
DOI: 10.1136/jmg.32.12.934
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the RET proto-oncogene and the von Hippel-Lindau disease tumour suppressor gene in sporadic and syndromic phaeochromocytomas.

Abstract: Phaeochromocytomas may occur sporadically, or as part of the inherited cancer syndromes multiple endocrine neoplasia (MEN) type 2, von Hippel-Lindau disease (VHL), and, rarely, in type 1 neurofibromatosis. In MEN 2, germline missense mutations have been found in one of eight codons within exons 10, 11, 13, 14, and 16 of the RET proto-oncogene. In VHL, germline mutations within one ofthe three exons are responsible for the majority of cases. To determine if somatic mutations similar to those seen in the germlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
71
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 29 publications
7
71
0
4
Order By: Relevance
“…Somatic VHL mutations are commonly involved in the tumorigenesis of hemangioblastomas, accounting for up to 50% of sporadic retinal and CNS hemangioblastomas [Maher et al, 1990a;Neumann et al, 1989;Oberstrass et al, 1996;Richard et al, 1998]. Interestingly, sporadic pheochromocytoma are rarely (3%) due to somatic VHL mutations [Bar et al, 1997;Eng et al, 1995;Glasker et al, 2001;Neumann et al, 1993;Sprenger et al, 2001]. However, up to 25% of seemingly sporadic pheochromocytomas actually have a germline VHL, NF-1, c-RET, or SDH mutations.…”
Section: Sporadic Diseasesmentioning
confidence: 99%
“…Somatic VHL mutations are commonly involved in the tumorigenesis of hemangioblastomas, accounting for up to 50% of sporadic retinal and CNS hemangioblastomas [Maher et al, 1990a;Neumann et al, 1989;Oberstrass et al, 1996;Richard et al, 1998]. Interestingly, sporadic pheochromocytoma are rarely (3%) due to somatic VHL mutations [Bar et al, 1997;Eng et al, 1995;Glasker et al, 2001;Neumann et al, 1993;Sprenger et al, 2001]. However, up to 25% of seemingly sporadic pheochromocytomas actually have a germline VHL, NF-1, c-RET, or SDH mutations.…”
Section: Sporadic Diseasesmentioning
confidence: 99%
“…[5][6][7][8] Moreover, the biological behavior of PCC has been analyzed in various immunohistochemical studies. [9][10][11][12] Unlike the mitotic count, which was found to be useless for predicting the malignant behavior of PCC, 13 the expression of Ki-67 is of prognostic significance.…”
mentioning
confidence: 99%
“…Germline mutations in SDHD (11q23) and SDHB (1p36.1), encoding subunits of the mitochondrial complex II (reviewed in Benn et al, 2002) have also been associated with familial phaeochromocytoma (Astuti et al,200la,b). However, the molecular pathogenesis of sporadic disease remains largely unknown, although somatic mutations have been identified in VHL (2%), RET (10%) and SDHD (6% ) (Eng et al, 1995;Hofstra et al, 1996;Gimm et al, 2000), yet none in SDHB (Astuti et al, 2001b) in these tumours. Loss of heterozygosity (LOH) studies have suggested that chromosome lp may be the site of at least two and possibly three tumour suppressor genes with a region at 1p36 being involved not only in phaeochromocytomas (Benn et al, 2000), but also in other endocrine and neural crest-derived tumours such as neuroblastoma (Williamson et al, 1997;Caron et al, 2001).…”
Section: Introductionmentioning
confidence: 99%